PERANAN ASAS ITIKAD BAIK DALAM KONTRAK BAKU (Upaya Menjaga Keseimbangan bagi Para Pihak) - Priyono, Ery Agus (Fakultas Hukum, Universitas Diponegoro, 2017)
Good faith is a value that becomes a benchmark in determining whether a contract is feasible or not to be implemented. Good faith is a filter based on morality and propriety for the existence of a contract, after the contract is declared to have been valid under the terms of the legal contract as stipulated in Article 1320 Civil Code. Standard contracts are contracts that tend to be unilateral and tend to violate the principle of freedom of contract. Contracts that in its formation are less involving the other party is often disifati as take it or leave it contract. This exposure aims to examine the function of the principle of good faith in judging a standard contract and its legal consequences if the principle is violated. Descriptive and normative analysis becomes an option in the discussion.sebagai conclusion then the result of the violation of the principle of good faith is the agreement null and void or can be canceled Keywords : Good faith, standard contract, unilateral,normative